Cooper pair transport in arrays of Josephson junctions = Cooperpaartransport in Feldern von Josephson-Kontakten - Zimmer, Jochen Oltmann (Experimental Condensed Matter Physics / Karlsruher Institut für Technologie, Physikalisches Institut, 2014)
this work, the fabrication, measurement and analysis of several one-dimensional SQUID arrays is described. The temperature and flux dependence of the thermally activated charge transport is analysed, and compared to a theoretical model.